Papillary renal cell carcinoma in two young adults with glycogen storage disease type Ia. Issue 1 (29th January 2020) - Perry, Ariane; Douillard, Claire; Jonca, Frederic; Glowacki, Francois; Leroy, Xavier; Caveriviere, Paul; Hubert, Aurélie; Labrune, Philippe
Abstract: Glycogen storage disease type Ia (GSD Ia) is a rare metabolic disease due to glucose‐6‐phosphatase deficiency. Chronic kidney disease is a frequent complication that may manifest itself by glomerular lesions and tubular dysfunction from the second decade of life. We report two young GSDIa patients with malignant renal tumor. The first patient was a 25‐year‐old man. He had chronic metabolic imbalance without kidney involvement. The tumor, a type 2 papillary renal carcinoma, was accidentally discovered during follow‐up. The second patient was a 27‐year‐old woman with chronic metabolic imbalance and chronic kidney involvement. The tumor, a grade 2 papillary carcinoma, was accidentally discovered during follow‐up. These two observations are, to date, the first to be reported. We suggest that annual monitoring of kidney imaging in GSDI patients should be systematic to detect renal cancer, from the second decade of life.